Job quality and labour market transitions: Evidence from Mexican informal and formal workers - Emily Conover; Melanie Khamis; Sarah Pearlman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In this paper we analyse informal work in Mexico, which accounts for the majority of employment in the country and has grown over time. We document that the informal sector is composed of two distinct parts: salaried informal employment and self-employment. Relative to self-employment and formal salaried employment, on average informal salaried workers have lower wages and lower job quality as measured by an index. Education plays a different role in job matches and job transitions, depending on the type of informal employment. Well-educated workers are more likely to use informal salaried work as a stepping stone into formal salaried work, and are less likely to leave the formal sector once there. Less well-educated workers have higher exit rates from formality and shift more across informal sector jobs. For these latter workers there is more evidence that informal salaried work represents jobs of last resort rather than jobs of opportunity.
Keywords: J3; J21; J46; O17; 330; informal work; job quality; transitions; Mexico